2020
DOI: 10.1186/s12879-020-05422-8
|View full text |Cite
|
Sign up to set email alerts
|

Differences in mortality in patients undergoing surgery for infective endocarditis according to age and valvular surgery

Abstract: Background Infective endocarditis (IE) is associated with high mortality. Surgery may improve survival and reduce complications, but the balance between benefit and harm is difficult and may be closely related to age and type of surgical intervention. We aimed to examine how age and type of left-sided surgical intervention modified mortality in patients undergoing surgery for IE. Methods By crosslinking nationwide Danish registries we identified patients with first-time IE undergoing surgical treatment 2000–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 47 publications
1
10
1
Order By: Relevance
“…7 Second, Huuskonen et al identified the female gender to be a protective factor for overall mortality. This runs contrary to prior findings 8,9 -though the related body of evidence is mixed. 10,11 The gender-outcome relationship is further complicated by both the fact the incidence of IE demonstrates a significant male predominance and the finding that women are less likely to undergo surgery for IE.…”
contrasting
confidence: 99%
“…7 Second, Huuskonen et al identified the female gender to be a protective factor for overall mortality. This runs contrary to prior findings 8,9 -though the related body of evidence is mixed. 10,11 The gender-outcome relationship is further complicated by both the fact the incidence of IE demonstrates a significant male predominance and the finding that women are less likely to undergo surgery for IE.…”
contrasting
confidence: 99%
“… 4 , 7 , 8 Age is currently included as a predictor in several risk scores and is regarded as an important independent predictor of mortality in patients with IE. 7 , 9 , 10 …”
Section: Introductionmentioning
confidence: 99%
“…Patients with DM duration 5-10 years, 10-15 years, and > 15 years were associated with a higher risk of IE compared with DM duration 0-5 years. Another study from the above mention Danish Registry [21], included 1767 patients with IE undergoing surgery, 735 patients < 60 years (24.1% female), 766 patients 60-75 years (25.8% female), and 266 patients ≥ 75 years (36.1% female). The proportions of patients undergoing surgery were 35.3, 26.9, and 9.1% for patients < 60 years, 60-75 years, and > 75 years, respectively.…”
Section: Discussionmentioning
confidence: 99%